Annuloplasty for Aortic Regurgitation in Infantile Takayasu Arteritis: A Case Report. Issue 4 (July 2020) - Linnemeier, Laura; Sharma, Richa; Srivastava, Nayan; Turrentine, Mark
Aortic regurgitation (AR) is a life-threatening complication of Takayasu arteritis (TA). Takayasu arteritis is a large-vessel vasculitis with a predominance in young adolescent and adult females. Inflammation involves the aorta and its major branches resulting in arterial dilatation, stenosis, aneurysm, occlusion, and thrombosis formation. Pediatric TA cases have been reported to also cause severe complications such as coronary aneurysms, retinopathy, and hypertension due to renovascular stenosis. In this report, we present a rare occurrence of infantile TA with severe AR requiring surgical intervention after failing medical therapy. Due to the patient's age and clinical status, a valve-sparing aortic annuloplasty with aortoplasty was performed.